Transnational Initiatives Towards Natural Resource Governance In Africa Post-2015 - Shaw, Timothy M. (Journal of Sustainable Development Law and Policy, 2025)
The 21st century is marked by a welcome proliferation of innovative forms of natural resource governance to advance sustainable development. This article sheds light on the background for this quite remarkable and unanticipated shift. It analyses the prospects for AMV advocacy and adoption by emerging state and non-state actors by the end of this decade, both in Africa and beyond. It examines these evolving perspectives and debates vis á vis 21st century globalization. It also identifies the unexpected and unprecedented range of transnational governance initiatives that have been proposed since the turn of the century. These continue to proliferate and compete, being refined in the process as the problematic notion of global governance continues to be a subject of considerable debate. It also extends the range of developmental challenges to include the burgeoning water-energy-food nexus.